Pemikiran Ismail Raji Al-Faruqi terhadap Dunia Pendidikan Islam - Apria Ningrum, Velida; Fikri Zuhriyah, Luluk (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The occurrence of a dichotomy between Islamic Education and Western Education has given birth to several reformers of Islamic Education. One of them is Ismail Raji al-Faruqi, a Muslim scholar with a background in Western Education who is actively involved in the world of Education. One of his phenomenal thoughts is related to the Islamization of knowledge, which is believed to be able to bring Islamic Education back forward and not just be a copycat of Western thought. In the context of Islamic Education, the knowledge that has not been integrated with Islamic values needs to be reviewed. In the Islamic Education curriculum, Al-Faruqi suggested instilling Islamic norms through the study of Islamic culture, both at the level of elementary education to higher education. The method used to examine Ismail Raji al-Faruqi's thoughts is a qualitative research method based on library research.